2020
DOI: 10.1016/j.jadr.2020.100013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Swahili version of the 9-item Patient Health Questionnaire (PHQ-9) among adults living with HIV compared to a community sample from Kilifi, Kenya

Abstract: Highlights Comparison of tool psychometrics between HIV-infected adults and community controls Internal consistency and test-retest reliability of the adapted Swahili PHQ-9 is good Swahili PHQ-9 is unidimensional overall, in HIV-infected adults and community sample Swahili PHQ-9 is invariant across group (HIV-infected vs controls), sex and age-group Swahili PHQ-9 exhibited good discriminant validity between the two par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
2
25
0
2
Order By: Relevance
“…The recommended optimal cut-off score of ≥10 for both PHQ-9 and GAD-7 [ 42 , 43 ], also applicable in sub-Saharan Africa [ 44 , 45 ], was used to define positive screen for depressive and anxiety symptoms. PHQ-9 and GAD-7 have locally been validated, showing good psychometric properties [ 46 , 47 ]. In the present study, the internal consistency alphas for PHQ-9 and GAD-7 were all good, 0.83 (95% CI 0.81, 0.86), and 0.86 (95% CI 0.84, 0.88), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The recommended optimal cut-off score of ≥10 for both PHQ-9 and GAD-7 [ 42 , 43 ], also applicable in sub-Saharan Africa [ 44 , 45 ], was used to define positive screen for depressive and anxiety symptoms. PHQ-9 and GAD-7 have locally been validated, showing good psychometric properties [ 46 , 47 ]. In the present study, the internal consistency alphas for PHQ-9 and GAD-7 were all good, 0.83 (95% CI 0.81, 0.86), and 0.86 (95% CI 0.84, 0.88), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…36 Studies have been conducted using PHQ-9 to diagnose for depressive symptoms among different populations in Kenya. 37,38 In a study conducted by Osborn et al, in 2019 about depression and anxiety symptoms, social support and demographic factors among Kenyan high school students showed high levels of depression symptoms (45.9% above clinical cutoff ). 39 In another study conducted in Kenya among HIV positive adolescents visiting Kenyatta National Hospital in 2019 showed that 1 in every 2 adolescents were showing depressive symptoms on PHQ-9 scale.…”
Section: Patient Health Questionnaire-9 (Phq-9)mentioning
confidence: 99%
“…The measure is scored on a 4-point Likert scale from '0' (not at all) to '3' (nearly every day) with total scores ranging from 0 to 27. PHQ-9 has previously been used in the study setting in Kenya, yielding good psychometric properties (37). This tool was translated and back-translated into Swahili using WHO guidelines then pre-tested in the study setting before being used in the current study.…”
Section: Caregivers' Mental Health Assessmentmentioning
confidence: 99%